BLENDED LEARNING METHOD BASED ON LOCAL WISDOM AS A SPIRITUAL GUIDANCE HOLY TRINITY COMMUNITY IN DISTRICT BENGKAYANG - Priska Vasantan (JETL (Journal of Education, Teaching and Learning), 2016)
Bengkayang is one of the districts the outermost in Indonesia. The district has limitations and underdevelopment in various fields, one of which is in the field of education. Writing this article aims to show that blended learning based on local wisdom is very helpful coaching Holy Trinity Community (HTC) in the district Bengkayang. It has been proven from previous studies, suggesting that coaching HTC with blended learning to be more flexible, effective and efficient . Blended learning has been applied HTC with a combination of conventional learning and e-learning in most areas in Indonesia. With the blended learning, the process of spiritual guidance becomes more flexible, effective and efficient so as to improve student in district Bengkayang.